Level of Business Acumen of UTP Interns – Students’ vs. Supervisors’ Perspectives - Ibrahim, M Yussoff; Khalid Ali, Khalidah; Abdul Karim, Z. A. (2009)
Business acumen has become an important element in achieving a successful career in all fields including engineering. It is a responsibility of any higher learning institution producing technical and engineering graduates to inculcate and strengthen the business acumen of their graduates. This paper develops an instrument to measure business acumen and examines the business acumen level of students at Universiti Teknologi PETRONAS from the students’ and supervisors’ perspectives. The business acumen of the students is assessed from their business knowledge during their thirty two (32) weeks industrial internship at various host companies. The data analyzed derived from a questionnaire survey on 48 students who have undergone the internship and 48 supervisors from the respective organizations that the interns have been attached to. Results obtained using the t - tests show that there is a significant difference between the assessment of business knowledge by the students (self –assessment) and by their supervisors. The students perceived themselves as having higher business knowledge compared to the ratings given by their supervisors. This paper also outlines recommendations and implications of the inclusion of the business acumen attribute in the SIIU Industrial Internship Programme.